Case report: Unusual coexistence between familial hypercholesterolemia and familial hypobetalipoproteinemia - Sasaki, Kei; Tada, Hayato; Kawashiri, Masa-aki; Ito, Toshimitsu (Frontiers in Cardiovascular Medicine, 2022)
Type 1 familial hypobetalipoproteinemia (FHBL1), characterized by low levels of apolipoprotein B (ApoB)-containing lipoproteins, elevation of transaminases, and hepatic steatosis, is a rare disease the prevalence of which is 1 in 3,000 among general population. Here we report an extremely rare family where phenotypes of familial hypercholesterolemia (FH) are canceled by coexistence of FHBL1 caused by an truncating mutation in apolipoprotein B (APOB).